1992
DOI: 10.1103/physreva.46.r1709
|View full text |Cite
|
Sign up to set email alerts
|

Collective response in globally coupled bistable systems

Abstract: The Rapid Communications section is intended for the accelerated publication of important new results. Since manuscripts submitted to this section are given priority treatment both in the editorial once and in production, authors should explain in their submittal letter why the work justifies this special handling. A Rapid Communication should be no longer than 4 printed pages and must be accompanied by an abstract. Page proofs are sent to authors We consider a system of globally coupled bistable systems under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
102
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(112 citation statements)
references
References 21 publications
10
102
0
Order By: Relevance
“…The above consideration shows that changing the number of elements in a small ensemble of coupled bistable elements to the optimum can significantly improve the sensitivity (cf. [5]). Moreover, changing its connectivity and/or coupling strength, a neuronal system can tune itself to signals with different frequencies.…”
Section: P H Y S I C a L R E V I E W L E T T E R S 4 February 2002mentioning
confidence: 99%
See 2 more Smart Citations
“…The above consideration shows that changing the number of elements in a small ensemble of coupled bistable elements to the optimum can significantly improve the sensitivity (cf. [5]). Moreover, changing its connectivity and/or coupling strength, a neuronal system can tune itself to signals with different frequencies.…”
Section: P H Y S I C a L R E V I E W L E T T E R S 4 February 2002mentioning
confidence: 99%
“…Stochastic resonance has been observed in numerous experiments [3]. Noteworthy, the order in a noise-driven system can have a maximum at a certain noise level even in the absence of periodic forcing, this phenomenon being called coherence resonance [4].Being first discussed in the context of a simple bistable model, stochastic resonance has been also studied in complex systems consisting of many elementary bistable cells [5]; moreover, the resonance may be enhanced due to coupling [6]. In this paper we discuss another type of resonance in such systems, namely, the system size resonance, when the dynamics is maximally ordered at a certain number of interacting subsystems.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Noise induced entrainment among coupled oscillators is found experimentally in Belousov-Zhabotinsky reactions and brain waves [7,8]. Stochastic resonance has been studied also in globally or locally coupled systems of many bistable elements and it was shown that the coupling can lead to the enhancement of the response [9,10,11,12]. Various types of Fokker-Planck equations have been used to study the stochastic resonance theoretically.…”
Section: Introductionmentioning
confidence: 99%
“…Basically, the stochastic resonance has four elements: nonlinear system, information-carrying input signal, noise, and performance measure [2]. Many kinds of nonlinear systems have demonstrated the stochastic resonance phenomena, such as static systems [3], dynamic systems [4] [19], discrete systems [21], and coupled systems [4] [20]. The traditional stochastic resonance requires the information-carrying signal to be weak and periodic.…”
Section: Introductionmentioning
confidence: 99%